The impact of public corruption on marketplace lending outcomes - Kaakeh, Abdulkader; Parker, Simon C. (Journal of Banking & Finance, 2025)
This study investigates the impact of public corruption on lending outcomes in the context of Marketplace Lending (MPL) platforms such as LendingClub. Utilizing data on over one million loans and state-level corruption metrics from the US Department of Justice, this research uniquely examines within-country variations in corruption. Our findings reveal a significant correlation between public corruption and loan defaults, with a 3 % increase in default rates per unit increase in corruption. Interest rates also rise by 9 basis points under similar conditions. These effects persist across various model specifications and robustness checks. We demonstrate that trust mediates the relationship between corruption and loan defaults, and that neither governance nor enforcement explains the observed impacts. This study contributes to the literature by linking corruption to individual financial behavior in fintech lending, highlighting the crucial role of trust in financial transactions.